A rare complication of pacemaker implantation. Issue 9 (17th July 2018) - Bazoukis, George; Panagiotakopoulos, Victor; Tsamatsoulis, Michalis; Saplaouras, Athanasios; Konstantinidou, Eleni; Tyrovolas, Konstantinos; Kolokathis, Angelos‐Michail; Sakellaropoulou, Antigoni; Kitsoulis, Panagiotis; Lakoumentas, Ioannis; Charitos, Christos; Sideris, Antonios
Key Clinical Message: Lead perforation is a life‐threatening rare complication of pacemaker or defibrillator lead implantation. Clinical examination, electrocardiogram, device interrogation, echocardiography, chest x‐ray, and chest computed tomography scan can help in the diagnosis. Clinicians should be aware because early diagnosis and treatment are the cornerstones for achieving a better outcome. Abstract : Lead perforation is a life‐threatening rare complication of pacemaker or defibrillator lead implantation. Clinical examination, electrocardiogram, device interrogation, echocardiography, chest x‐ray, and chest computed tomography scan can help in the diagnosis. Clinicians should be aware because early diagnosis and treatment are the cornerstones for achieving a better outcome.